Mangrove Tree Community Structure And Community Participation Of Mangroves In Ciletuh-Palabuhan Ratu Geopark, Sukabumi - Cahyadi, Ferry Dwi; Agustin, Nisa Rahayu; Prasetiyo, Himawan (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
The Cikadal mangrove forest area is part of the Ciletuh-Palabuhanratu Geopark in Mandrajaya Village. The area of ​​this mangrove forest is 5 ha and has been reforested. The purpose of this research is to describe the community structure of mangrove plants after reforestation and the participation of the community in the Ciletuh-Palabuhanratu Geopark. Mangrove structure data collected using PCQ (Point Centered Quarter Method) as well as a questionnaire for community knowledge and participation in managing mangroves. The results showed that there were two types of mangroves in this area, namely Avicinnea officinalis and Rhizophora apiculata. The results of the Important Value Index with the highest score being 182.7, Rhizophora apiculata while for Avicinnea officinalis was 117.3. Knowledge of local communities about mangroves and their conservation and local community participation is in the medium-high category.